THE EFFECT OF CORPORATE GOVERNANCE AND FIRM SIZE ON EARNINGS MANAGEMENT - Wijaya, Deni; Chandra, Santoso (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to provide empirical evidence for every investor who wants to invest in a company listed on the Indonesian stock exchange. This study also uses calculations in the form of leverage and company size so that investors can find out which companies are experiencing losses and profits.This research data consists of financial ratios from the financial statements of manufacturing companies that are listed in Indonesia for 3 years 2018 to 2020. This study discusses 7 independent variables and also uses multiple regression models.The results showed that firm size, company losses, board of director, leverage and audit committee tenure had an effect on earnings management while the independent commissioner and managerial ownership have no effect on earning management.